Harmine, an inhibitor of the type III secretion system of Salmonella enterica serovar Typhimurium - Shi, Yunjia; Chen, Xindi; Shu, Jingyan; Liu, Yang; Zhang, Yong; Lv, Qianghua; Wang, Jianfeng; Deng, Xuming; Liu, Hongtao; Qiu, Jiazhang (Frontiers in Cellular and Infection Microbiology, 2022)
New therapeutic strategies for clinical Salmonella enterica serovar Typhimurium (S. Typhimurium) infection are urgently needed due to the generation of antibiotic-resistant bacteria. Inhibition of bacterial virulence has been increasingly regarded as a potential and innovative strategy for the development of anti-infection drugs. Salmonella pathogenicity island (SPI)-encoded type III secretion system (T3SS) represents a key virulence factor in S. Typhimurium, and active invasion and replication in host cells is facilitated by the secretion of T3SS effector proteins. In this study, we found that harmine could inhibit T3SS secretion; thus, its potential anti-S. Typhimurium infection activity was elucidated. Harmine inhibits the secretion and expression of T3SS effector proteins and consequently attenuates the S. Typhimurium invasion function of HeLa cells. This inhibition may be implemented by reducing the transcription of pathogenesis-related SPI-1 transcriptional activator genes hilD, hilC, and rtsA. Harmine improves the survival rate and bacterial loads of mice infected with S. Typhimurium. In summary, harmine, an effective T3SS inhibitor, could be a leading compound for the development of treatments for Salmonella infection.